RANCANG BANGUN APLIKASI PENJUALAN JERUK LEMON DAN SARI JERUK CALIFORNIA BERBASIS WEB DENGAN METODE WATERFALL (STUDI KASUS PADA PT KAYU LAPIS ASLI MURNI) - Zulfariansyah, Muhammad; Septian, Septian; Dedy, Dedy (Universitas Nahdlatul Ulama Kalimantan Timur, 2024)
The application for selling lemon and California orange juice at PT Kayu Lapis Asli Murni is a web-based application designed to facilitate the Secretariat Department's admin in managing the sales data and harvest results of lemon and the production of California orange juice. It automates the calculation of stock inventory, sales revenue, and handles the generation of sales reports. The application's analysis and design process involved tools such as Flow of Document, Context Diagram, Data Flow Diagram, Entity Relationship Diagram, and Hierarchy Input Process Output. The system development method employed is the Waterfall method. This application is constructed using Sublime Text 3 software with HTML, CSS, and PHP programming languages. Database management and data management systems utilized PhpMyAdmin and MySQL software. Additionally, the Black Box method is employed as the testing method to ensure that all functions operate effectively. Research results indicate that the application's implementation and testing fall into the 'good' category, as it facilitates the Secretariat Department's admin in data processing, streamlines report generation for decision-making, and all features in the application function as intended.